RATIONALITY ANALYSIS OF SWAMEDICATION OF USE OF URIC ACID DRUG IN THE COMMUNITY OF BINTAUNA BEACH AND KOPI VILLAGE, BINTAUNA DISTRICT, BOLAANG MONGONDOW NORTH REGENCY - Dwi Audia Hassan; Rini Daud Supu; Adnan Malaha (Journal of Health, Technology and Science (JHTS), 2023)
Uric acid is the condition that occurs by an excessive or abnormal levels of uric acid because the body cannot normally secrete it. The purpose of this study wasexamine the pattern of self-medicateddrug and to identify the prevalence of the self-medicated of uric acid drug that rationally usedin the communities of Bintauna Pantai and Kopi Village, Bintauna District, Bolaang Mongondow Utara Regency. This study used quantitative descriptive method. The data was collected using survey to analyze the rationalizations of self-medicated uric acid drug use in the communities that specifically suffer from uric acid condition. The result of this study was analyzed using the data that collected from the questionnaire instrument to see how rational the use of uric acid drugs is by the people of Bintauna Pantai and Kopi Village, Bintauna District, Bolaang Mongondow Utara Regency. The rationality test showed that 94,5 % of respondents used the drugs rationally, and the other 5,5% used the drugs irrationally.